A Lipidomics Approach to Identifying Key Lipid Species Involved in VEGF‐Inhibitor Mediated Attenuation of Bleomycin‐Induced Pulmonary Fibrosis. Issue 3 (19th January 2018) - Kulkarni, Yogesh M.; Dutta, Sucharita; Iyer, Anand Krishnan V.; Wright, Clayton A.; Ramesh, Vani; Kaushik, Vivek; Semmes, Oliver John; Azad, Neelam
Abstract : Purpose: Poor molecular characterization of idiopathic pulmonary fibrosis (IPF) has led to insufficient understanding of the pathogenesis of the disease, resulting in lack of effective therapies and poor prognosis. Particularly, the role of lipid imbalance due to impaired lipid metabolism in the pathogenesis of IPF has been poorly studied. Experimental design: The authors have used shotgun lipidomics in a bleomycin (BLM) mouse model of pulmonary fibrosis with vascular endothelial growth factor (VEGF)‐inhibitor CBO‐P11 as a therapeutic measure, to identify a comprehensive set of lipids that contribute to the pathogenesis of pulmonary fibrosis. Results: The authors report that attenuation of BLM‐induced fibrotic response with CBO‐P11 cotreatment is accompanied by a decrease in total lipid content and specific downregulation of lipids, which are upregulated in response to BLM treatment. Conclusion and clinical relevance: Dysregulated lipids identified in this study hold the potential of being future biomarkers for IPF.